Mechanisms of metabolic transition in hypertrophic cardiomyopathy - Tan, Conghao; Guo, Zhexuan; Zhou, Junjie; Yuan, Wei (Frontiers in Physiology, 2025)
Hypertrophic cardiomyopathy (HCM) is a prevalent hereditary cardiovascular disease that affects individuals worldwide. While current treatments have improved the prognosis for many patients, HCM continues to impose a significant burden on global healthcare systems. Understanding its underlying mechanisms, particularly the role of metabolic transition, is crucial for enhancing diagnosis and treatment strategies. One of the most promising areas of research in HCM is the study of metabolic transition. This process, which involves significant changes in energy production and consumption within cardiac cells, has become increasingly recognized as a key factor in the disease’s progression. In HCM, glucose metabolism is markedly altered. The heart increasingly relies on glycolysis for energy production, while the aerobic oxidation of glucose is impaired. These changes are accompanied by alterations in the activity of glucose transporter proteins and key enzymes involved in glycolysis. Such abnormalities are closely associated with myocardial ischemia, fibrosis, and an increased risk of acidosis in cardiomyocytes, which in turn affects calcium cycling and cardiac diastolic function. Lipid metabolism is significantly altered in HCM. There is a defect in fatty acid β-oxidation, leading to the accumulation of ceramides and sphingomyelins in cardiomyocytes. Additionally, changes in ketone body metabolism occur as an adaptive response to energy deficiency, which may further affect cardiac function. Amino acid metabolism is also altered in HCM. Elevated levels of branched-chain amino acids have been observed, and these metabolites are strongly associated with cardiac remodeling and the development of insulin resistance. These changes further contribute to the maladaptive processes in HCM. A comprehensive understanding of the metabolic transition process in HCM is essential for unraveling the disease’s pathogenesis. Such insights could pave the way for novel therapeutic strategies, ultimately improving patient outcomes and quality of life.